Online and search costs: koan to unknowns. - Arnold SE (Online (0146-5422))
Is online access sweeps into everyday life, its push buries common sense in a pile of bits and bytes. In this article I use online and search--though technically quite different--as synonyms because both share a 'cost challenge.'